Stained glass artwork at the Apse - Ghosh, Ayan (2023)
Glass panels at the apse of St. Thomas Church. The left panel shows the 'Risen' Jesus whose wound is inspected by 'doubting' St. Thomas. The central panel depicts Jesus on the cross, surrounded by angels. Below the crucifixion, Mother Mary holds the infant Jesus on her lap. The right panel shows the Ascension of Jesus to heaven, witnessed by the Apostles.